PTH-103 The Management And Assessment Of Incidental Pancreatic Cysts On Computer Tomography In A Non-pancreatic Centre. (9th June 2014) - Kadir, S; Sheikh, U; Iqbal, J
Abstract : Introduction: With increased use and sensitivity of cross sectional imaging more incidental pancreatic cystic lesions are found. Studies have demonstrated a prevalence of 2.5% of cystic pancreatic lesions in asymptomatic patients on MRI and CT scanning. Cystic lesions have a wide variety of radiological appearances and prognostic outcomes. We aimed to review cases found to have incidental pancreatic cysts on CT scanning and ascertain the concordance between CT and EUS and the management of such lesions in a non-pancreatic centre. Methods: We retrospectively reviewed patients undergoing EUS for pancreatic cystic lesions found on incidentally on CT scan between 2010 and 2012. Twenty-five patients were included. Solid lesions with a cystic component were excluded. Results: There were 15 female; 10 male. Indications for CT scan included abdominal pain 32%; weight loss 16%; jaundice and suspected stone disease with abnormal USS 16%. In all cases there was no preceding clinical suspicion of pancreatic cysts/disease. Median number of cysts was 1 (1–4); mean size 3 cm (1–11 cm). In 70% of cases the cyst was >3 cm; and <3 cm in 30%. They were located in the HOP 36%; BOP 32%; TOP 16%; NOP 4%; multiple sites 12%. The cyst was aspirated +/- biopsy in 12 (48%) cases, of which in 2 (16%) this changed the CT diagnosis. Final diagnosis was pseudocyst 10 (40%); IPMN 6 (24%); simple cyst 2 (8%); serous cystadenoma 2 (8%); mucinous cystadenoma (MCA) 1 (4%); cystic adenoca 1 (4%); wegeners cyst 1 (4%); renal cyst 1 (4%). In 32% (8 cases), the EUS findings were inconsistent with CT findings, due to IPMN and MCA in the vast majority. Greatest concordance between EUS and CT findings was in the diagnosis of pseudocysts. Conclusion: Increasing number of asymptomatic pancreatic cysts found incidentally will undoubtedly cause increased referrals to tertiary pancreatic centres. EUS is a better imaging modality with additional benefit of attaining samples. Performing EUS +/- cyst FNA provided an alternative diagnosis to CT in a significant percentage (32%) of patients and helped streamline referrals for tertiary opinion. EUS should be considered in all patients presenting with incidental pancreatic cysts on cross-sectional imaging. This may be performed at the index hospital (if non-pancreatic centre) and should not be restricted to tertiary HPB centres if operator experience and confidence allows. Disclosure of Interest: None Declared.